Adapting Content Delivery to Limited Resources and Inferred User Interest. (8th July 2008) - Plesca, Cezar; Charvillat, Vincent; Grigoras, Romulus
Abstract : This paper discusses adaptation policies for information systems that are subject to dynamic and stochastic contexts such as mobile access to multimedia web sites. In our approach, adaptation agents apply sequential decisional policies under uncertainty. We focus on the modeling of such decisional processes depending on whether the context is fully or partially observable. Our case study is a movie browsing service in a mobile environment that we model by using Markov decision processes (MDPs) and partially observable MDP (POMDP). We derive adaptation policies for this service, that take into account the limited resources such as the network bandwidth. We further refine these policies according to the partially observable users_ interest level estimated from implicit feedback. Our theoretical models are validated through numerous simulations.